1994
DOI: 10.1007/bf01755879
|View full text |Cite
|
Sign up to set email alerts
|

Mammary carcinoma cell lines of high and low metastatic potential differ not in extravasation but in subsequent migration and growth

Abstract: We examined the extravasation and subsequent migration and growth of murine mammary tumor cell lines (D2A1 and D2.OR) which differ in their metastatic ability in lung and liver, invasiveness in vitro and expression of the cysteine proteinase cathepsin L. In light of the differences in invasiveness and cathepsin L expression, we hypothesized that during hematogenous metastasis the two cell lines would differ primarily in their ability to extravasate. We used in vivo videomicroscopy of mouse liver and chick embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 14 publications
7
91
2
Order By: Relevance
“…Similar results have also been obtained using tumor cell lines with low and high metastatic potential in mice and in the CAM assay. No difference in the extravasation rate was observed, whereas subsequent migration in the tissue and the rate of tumor cell proliferation were different (Koop et al, 1996;Morris et al, 1994). Thus whereas the spreading of the tumor cells into various organs from the primary tumor appears to be an efficient process, the subsequent growth of these metastasized cells is a rate-limiting step.…”
Section: Metastasismentioning
confidence: 90%
“…Similar results have also been obtained using tumor cell lines with low and high metastatic potential in mice and in the CAM assay. No difference in the extravasation rate was observed, whereas subsequent migration in the tissue and the rate of tumor cell proliferation were different (Koop et al, 1996;Morris et al, 1994). Thus whereas the spreading of the tumor cells into various organs from the primary tumor appears to be an efficient process, the subsequent growth of these metastasized cells is a rate-limiting step.…”
Section: Metastasismentioning
confidence: 90%
“…It has been reported that mammary carcinoma cells are localized beneath the capsule of Glisson 24 hr after metastasis induction. 62 Griffini et al 42 showed that 3 weeks after inoculation of CC531s cells, large metastatic nodules occur just beneath the capsule of Glisson, while few smaller and well-encapsulated nodules are only located in the center of the liver. Our experiments also demonstrated that cancer cells escaping the first line of immune defense during the first day of metastasis in both normal and NK-depleted rats were localized in the sinusoids, in the space of Disse or between parenchymal cells in a specific region that lies within 250 m beneath the capsule of Glisson.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2-and control virus-infected H16N2 cells were labeled with Fluoresbrite carboxylated polystyrene nanospheres of 48 nm diameter (Polysciences) as described (26). See Supporting Methods for details.…”
Section: Selection Of Patients and Tissue Microarray Developmentmentioning
confidence: 99%